Terahertz spectroscopy study of the topological insulator Bi2Se3 thin film - Ng, Yi Ming (2016)
Topological insulators are a distinct class of materials with insulating bulk states and conducting surface states, and they are a major focus for research in Condensed Matter Physics. In this project, a topological insulator, Bi2Se3 thin film, is grown by molecular beam epitaxy (MBE) which is 32 QL thick. It is investigated using Terahertz-Time Domain Spectroscopy (THz-TDS). Bi2Se3 has been around since the 1950s and it is only until recently that more attention was paid to it as a topological insulator. It shows particular promise for technological applications such as a THz photodetector.